2013
DOI: 10.7150/ijms.6884
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Profiling Revealed Promoter Hypermethylation-induced Silencing of p16, DDAH2 and DUSP1 in Primary Oral Squamous Cell Carcinoma

Abstract: Background: Hypermethylation in promoter regions of genes might lead to altered gene functions and result in malignant cellular transformation. Thus, biomarker identification for hypermethylated genes would be very useful for early diagnosis, prognosis, and therapeutic treatment of oral squamous cell carcinoma (OSCC). The objectives of this study were to screen and validate differentially hypermethylated genes in OSCC and correlate the hypermethylation-induced genes with demographic, clinocopathological charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 52 publications
1
35
0
Order By: Relevance
“…Genomic studies have not identified a common mutation or deletion, but a recent DNA methylation screen identified significantly increased promoter hypermethylation in over 80% of oral cancer tissues (18). Pharmaceutical intervention to induce DUSP1 expression, with rosiglitazone and mapracorat, are currently being explored in vitro with promising results (19,20).…”
Section: Resultsmentioning
confidence: 99%
“…Genomic studies have not identified a common mutation or deletion, but a recent DNA methylation screen identified significantly increased promoter hypermethylation in over 80% of oral cancer tissues (18). Pharmaceutical intervention to induce DUSP1 expression, with rosiglitazone and mapracorat, are currently being explored in vitro with promising results (19,20).…”
Section: Resultsmentioning
confidence: 99%
“…Only selected differentially hypermethylated probes in OSCC patients that passed the filtration criteria were then subjected to Partek Genomics Suite 6.5 analysis (Partek Inc., USA) for gene selection. DOI:http://dx.doi.org/10.7314/APJCP.2014.15.20.8957 Promoter Hypermethylated Genes in Primary Oral Squamous Cell Carcinoma of TP73, PIK3R5, and CELSR3 were selected from the gene list based on the selection criteria form our previous experiment (Khor et al, 2013).…”
Section: Microarray Data Analysismentioning
confidence: 99%
“…Analyses carried out on DNA methylation patterns show that this process can be used as a biomarker for early diagnosis as well as for classification, prognosis, and therapy of human cancers [6]. Previous studies have identified the methylation of the promoter regions of over 40 tumor suppressor genes in oral squamous cell carcinoma and precancerous lesions, such as CDKN2A, MGMT, DAPK1, RUNX3, and p14 ARF [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 98%